The Influence of Fear of Missing Out (FoMO) on Purchase Decisions through Impulsive Behavior: Evidence from TikTok Pop Mart Live Streaming - Salsabiila Putri Jamaludin; Ati Mustikasari; Alma Syifa Maulidina (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Through this study, I aim to analyze the impact of Fear of Missing Out (FoMO) on purchasing decisions through impulsive behavior between TikTok Pop Mart live streaming consumers. The swift expansion of live streaming commerce has boosted consumer interest tendency to make spontaneous purchases influenced by emotional and psychological factors, particularly FOMO. This study employed applying a quantitative design through Structural Equation Modeling–Partial Least Squares (SEM-PLS).The researchers collected data using questionnaire distributed to TikTok users who had watched Pop Mart live streaming sessions and purchased Pop Mart products, with purposive sampling. The research variables consisted of Fear of Missing Out (FoMO) identified being an independent element, impulsive behavior as an intermediary, and purchasing decisions as the dependent variable. Findings indicate that FoMO exerts a significant favorable impact on purchase decisions. In addition, impulsive behavior has been identified as significantly act as an intermediary between FoMO and purchasing decisions during TikTok Pop Mart live streaming sessions. This research suggests that emotional triggers through live streaming commerce can increase consumers' impulsive tendencies and encourage spontaneous purchase behavior. This paper adds to the existing literature on knowledge about consumer actions within social commerce and provides managerial implications for live streaming marketing strategies.